Construction of interface-engineered two-dimensional nanohybrids towards superb fire resistance of epoxy composites. (January 2022) - Gong, Kaili; Yin, Lian; Zhou, Keqing; Qian, Xiaodong; Shi, Congling; Gui, Zhou; Yu, Bin; Qian, Lijun
Abstract: Interfacial interaction played a crucial role in the performance of nanofiller-reinforced polymer composites. Here, an interface-engineered strategy was adopted to establish the strong interfacial linkage between phosphorus-doped cerium oxide (P-CeO2 ) and EP via introducing polyaniline (PANI) coating, and then endow EP composites with superb fire resistance. The as-prepared P-CeO2 @PANI nanohybrids were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR), X-ray photoelectron spectroscopy (XPS), thermogravimetry analysis (TGA) and scanning electron microscopy (SEM), respectively. Subsequently, P-CeO2 @PANI nanohybrids were incorporated into EP matrix to probe their influences on the thermal properties, flame retardancy and mechanical properties of EP composites. The coated PANI could strengthen the interfacial adhesion between P-CeO2 and EP by covalent bonding, achieving a good dispersion state in EP matrix. Moreover, the introduction of P-CeO2 @PANI nanohybrids led to the decreasing peak heat release rate (PHRR), total heat release (THR), peak CO production rate (PCO) and peak CO2 production rate (PCO2 ), with the reduction of 21%, 26%, 40% and 31%, respectively. Additionally, the introduction of P-CeO2 @PANI enhanced cross-linking density and dynamic mechanical properties of EP composites. In conclusion, the reinforced interfacial interactions promoted the dispersion of interface-engineered nanofiller, which together with the lamellar barrier effect and catalytic effect of P-CeO2 @PANI hybrids, contributed to the enhancements of the thermal properties, fire safety and mechanical properties of EP composites.